(The Effects Temperature and rotationSpeed of Mollen Dryer on The Characteristic s of aloe vera co-crystalization) - Indra Neffi Ridwan; Enny Hawani Lubis; Putty Meuraxa; Yanna Holianawaty (Warta Industri Hasil Pertanian, 2005)
The research is aimed to study the effect of temperature and rotation speed of mollen dryer on the characteristic of (aloe vera linn)co-crystalization.The temperature usedwere 55 degree C,60 degree C,and 65 degree C.The rotation speeds of mollen dryer are 12 rpm, 18 rpm, and 24 rpm respectively.The experimental design was the factorial random design with two replications. The result showed the best product was obtained from temperature of 60 degree C and 18 rpm rotation speed of mollen dryer.The composition of the dried aloe vera is :total sugar 56.18%,moisture content 0,84%,fiber content 0.92% and the solubility is 98.31%.While organoleptically (taste,texture,aroma,and appearane)the product was acceptable